Preparedness of lecturers in integrating gender responsiveness in the curriculum in community colleges in the Eastern Cape - Tawana, X.; Higgs, P. (South African Journal of Higher Education, 2024)
This article sets out to explore the problem of the preparedness of lecturers in integrating a gender responsive curriculum in Community Colleges the Eastern Cape. It is essential to understand why lecturers do not incorporate a gender responsive curriculum to help Community Colleges in the Eastern Cape develop fresh approaches that will directly address the specific requirements of both males and females. This article adopts a phenomenological research design to determine lecturer’s perceptions and perspectives on how well as they considered themselves ready in ensuring a gender responsive curriculum in the Community Colleges in the Eastern Cape. The methodology considered to be most suitable for grounding this study was a critical research methodology because approaches like positivism and interpretivism do not challenge inferences to increase the value of evidence collected on the ground. The required research data were gathered using semi-structured interview on eight (8) lecturers who volunteered to participate in this study. The research findings revealed that lecturers are not prepared to ensure a gender responsive curriculum in Community Colleges in the Eastern Cape. Their viewpoints therefore suggested that preparedness for the integration of a gender responsive curriculum is essential in Community Colleges.